Gambaran Kualitas Pelayanan Kesehatan Pada Pasien Rawat Jalan Di Puskesmas Lateri Kecamatan Baguala Kota Ambon - Epi Dusra (Jurnal Sains dan Kesehatan, 2020)
Quality of service not yet optimal because many basic health facilities do not meet the standards of service readiness and the absence of standard health service guidelines. Puskesmas, which are first-level health facilities, are at the forefront of efforts to reduce inequalities in health development in all regions. The purpose of this study was to describe the quality of health services for outpatients at the Lateri Public Health Center in Ambon City in 2020. This type of research is a quantitative study using a descriptive design with a sample of 137 respondents by using accidental sampling. The instruments used were questionnaires and writing instruments. The data analysis used was univariate analysis. Research resultIt is known that the tangibles variable (evidence / form) the respondent answered did not support more with it, the number of respondents was 69 people (50.4%). Reliability (Reliability), respondents answered more not according to amounting to 69 (50.4%). For the responsiveness variable (responsiveness), respondents answered responsiveness amounted to 83 people (60.6%), good Assurance (Assurance) amounted to 95 people (69.3%) while the empathy variable (empathy) who answered was 97 people (70.8 %).It is concluded that almost all of the dimensions of service quality found in this study are good.